Explanation:
x²-8x+15= 0
x²-2*1*4*x+ 16-1=0
x²-2*1*4*x+4² = 1
(x-4)² = 1
x-4 =1 or x-4= -1
x= 5 or x=3
so the solutions are 5 and 3
r²+18r+56=0
r²+2*1*9*r+ 81-25=0
r²+2*1*9*r+9² = 25
(r+9)² = 25
r+9 = 5 or r+9 = -5
r= -4 or r = -14
so the solutions are -4 and -14
x²+2x-24=0
x²+2*1x +1-25=0
x²+2*1*x+1² = 25
(x+1)² = 25
x+1= 5 or x+1= -5
x = 4 or x= -6
so the solutions are 4 and -6
p²+12p-54 = 0
p²+2*6*p+36-90=0
p²+2*6*p+6² = 90
(p+6)² = 90
p+6 = √90 or p+6 = -√90
p = √90-6 or p= -√90-6
m²-6m-55= 0
m²-2*3*m+3²-64=0
(m-3)² = 64
m-3 = 8 or m-3 = -8
m= 11 or m= -5